If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -17 + 3x = 5x + 7 Reorder the terms: -17 + 3x = 7 + 5x Solving -17 + 3x = 7 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -17 + 3x + -5x = 7 + 5x + -5x Combine like terms: 3x + -5x = -2x -17 + -2x = 7 + 5x + -5x Combine like terms: 5x + -5x = 0 -17 + -2x = 7 + 0 -17 + -2x = 7 Add '17' to each side of the equation. -17 + 17 + -2x = 7 + 17 Combine like terms: -17 + 17 = 0 0 + -2x = 7 + 17 -2x = 7 + 17 Combine like terms: 7 + 17 = 24 -2x = 24 Divide each side by '-2'. x = -12 Simplifying x = -12
| 12w+w=5-2w | | 18+2y=4y-8 | | -2x-70=29+9x | | 3(a+7)=-6 | | 7x+5x-80=136 | | 5=3x-13 | | 7y-9(5y-5)= | | 6x^2=13x-6 | | (x)+(x+2)=23 | | (M+3)-2m=3(m-3) | | 5x+67=180 | | 25x^2+30x=-9 | | 4(-4x+4)=208 | | -2x^3y+4x^2y^2+70xy^3=0 | | -15-(-2)-(11-6)= | | 4+4x=-7x-40 | | 210=10*w*3 | | 2u+18=7(u+4) | | x-5+x-5+x-5+x-5= | | 136=x^2+16X | | -10-9x=-8x+7 | | -8x+4(x-8)=-36 | | -x*6=-18 | | 3x=4-7x^2 | | 9x+7=180 | | 108+4y=-2y | | (x)+(x+2)=33 | | 6y+3=6-2y | | 5p+d*r=r-7 | | 6x-10=-70-4x | | 5(2x+61x+294)=0 | | 10+3y=0 |